The Principle of Recurrences in Algimantas Mackus Poetry - Unikauskas, Giedrius (Respectus Philologicus, 2001)
Mackus' poetry can be evaluated as a series of recurrences, where every stage reveals the same situation differently - returns to the issue of meaning anew. Various means of expression are realized in order to give a name to a meaning and sense. The poems of the first collection "Elegy" reflect uneven relationship between traditional poetry and individual language, in which individuality is only the excess of meanings, which refers to other meanings within the frame of traditional main means to express poetry canons. The poems of "His Earth" and "Recurrences" collection cycle reflect the very essence of poetry - a variety of possibilities to name meanings what conditions multi-meanings, which, however, remain indifferent to an imaginative meaning. In the last collection - "Unornamented Generation of Language", "Foster-children" and "Chapel B" - a new poetic expression is revealed, which is based on imaginative meanings in order to negate a bilingual condition - incongruous meanings are the only expressions of an adequate language to itself, whereas a continuous conflict - the only reference to a meaning. Allegory, which is based on real connections of meanings, becomes the main means to express poetry.
Keywords: individual language; excess of meanings; implied meaning